Sex-Associated Differential mRNA Expression of Cytokines and Its Regulation by Sex Steroids in Different Brain Regions in a Plasmodium berghei ANKA Model of Cerebral Malaria - Martha Legorreta-Herrera; Karen E. Nava-Castro; Margarita I. Palacios-Arreola; Rosalía Hernández-Cervantes; Jesús Aguilar-Castro; Luis A. Cervantes-Candelas; Jorge Morales-Montor (Mediators of Inflammation)
Cerebral malaria (CM) is the major complication associated with death in malaria patients, and its pathogenesis is associated with excessive proinflammatory cytokine production. Notably, the severity and mortality of natural infections with Plasmodium are higher in males than females, suggesting that sexual hormones influence both the pathogenesis of and immune response in CM. However, no studies on inflammation mediators in the brains of both sexes have been reported. In this work, the mRNA expression levels of the proinflammatory cytokines IL-1β, IFN-γ, TNF-α, and IL-2 were measured in the preoptic area, hypothalamus, hippocampus, olfactory bulb, frontal cortex, and lateral cortex regions of gonadectomized female and male CBA/Ca mice infected with P. berghei ANKA (a recognized experimental CM model). Our findings demonstrate that both infection with P. berghei ANKA and gonadectomy trigger a cerebral sex dimorphic mRNA expression pattern of the cytokines IL-1β, TNF-α, IFN-γ, and IL-2. This dimorphic cytokine pattern was different in each brain region analysed. In most cases, infected males exhibited higher mRNA expression levels than females, suggesting that sexual hormones differentially regulate the mRNA expression of proinflammatory cytokines in the brain and the potential use of gonadal steroids or their derivates in the immunomodulation of cerebral malaria.